1997
DOI: 10.1111/j.1095-8649.1997.tb01355.x
|View full text |Cite
|
Sign up to set email alerts
|

Postembryonic development of the cephalic region in Heterobranchus longifilis

Abstract: At hatching, Heterobranchus longifilis does not display any primordia of the cephalic skeleton. The latter appears 12 h post-hatching and develops in three stages up to day 16. The first stage (12 h to 2 days) involves almost exclusively the development of the chondrocranium. During the second period (days 3-8), dermal elements of the splanchnocranium appear. The final stage is marked by resorption of the cartilages, progressively replaced by ossifications (days 10-16). At their appearance the elements of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
75
0
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(82 citation statements)
references
References 33 publications
3
75
0
4
Order By: Relevance
“…The development of the branchial arches in C. aeneus differs from the situation described in siluriform fish up to this point. Generally, in siluriformes, chondrification in each arch starts with the ceratobranchials, followed by the hypobranchials and basibranchials, and eventually the epi-and pharyngobranchials (Srinivasachar, 1959;Adriaens and Verraes, 1997;Vandewalle et al, 1997). In C. aeneus, however, we found that all different elements arose simultaneously and continuously with each other.…”
Section: Neurocraniummentioning
confidence: 85%
See 2 more Smart Citations
“…The development of the branchial arches in C. aeneus differs from the situation described in siluriform fish up to this point. Generally, in siluriformes, chondrification in each arch starts with the ceratobranchials, followed by the hypobranchials and basibranchials, and eventually the epi-and pharyngobranchials (Srinivasachar, 1959;Adriaens and Verraes, 1997;Vandewalle et al, 1997). In C. aeneus, however, we found that all different elements arose simultaneously and continuously with each other.…”
Section: Neurocraniummentioning
confidence: 85%
“…However, several studies indicate that siluriform chondrocrania are generally limited in complexity at the time of hatching. Species like Chrysichthys auratus (Claroteidae) and Heterobranchus longifilis and Clarias gariepinus (Clariidae) show little to no chondrification at hatching while the chondrocranium in hatchlings from other species like Heteropneustes fossilis (Heteropneustidae) is only slightly developed (Srinivasachar, 1959;Adriaens and Verraes, 1997;Vandewalle et al, 1997Vandewalle et al, , 1999. Studies on species of the Loricarioidea superfamily, like Ancistrus cf.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In most cases, early skeletal development occurs first in elements that are necessary for feeding and respiration and therefore affect the survival of young larvae (Vandewalle et al 1997;Wagemans and Vandewalle Fig. 3 Developmental sequences of the jaw bone, palate, and opercular series of Sebastes koreanus in preflexion larval to juvenile stages (lateral views).…”
Section: Discussionmentioning
confidence: 99%
“…However, the timing of the ossification of the hyomandibular is highly variable (Kim and Han 1991;Kim et al 1993;Kim et al 1997;Byun et al 2012). In most teleostei, the parasphenoid is the first element to ossify, except in some species in which the parasphenoid ossifies simultaneously with the frontals (Pagrus major; Matsuoka 1987) or the basioccipital (Heterobranchus longifilis; Vandewalle et al 1997), or is ossified after the ossification of the frontals (Scophthalmus maximus; Wagemans et al 1998). In S. koreanus, the first-ossified elements in the neurocranium (at 6.27 mm BL) are the (Fig.…”
Section: Discussionmentioning
confidence: 99%